Influence of Different Feeding Methods of NPK and Boron on Vegetative Growth and Biochemical Attributes of Dragon Fruit [Hylocereus costarecencis] - Lavkush Pandey; Sanjay Pathak; Kuldeep Kumar Shukla; Alok Kumar; Vartika Singh; Sipra Mohapatra (Applied Fruit Science, 2026)

Elucidating the Conjoint Effect of Nano, Conventional and Bio-Fertilizer on Steering Sugarcane Productivity, Quality and Soil Health - Mona Nagargade; Vishal Tyagi; Dileep Kumar; Sudhir Kumar Shukla; Preeti Singh; Rajeev Kumar; Ashwini Dutt Pathak; V. P. Jaiswal; M. K. Tripathi; A. P. Dwivedi; Lalan Sharma; Sanjay Singh Rathore; et al. (International Journal of Plant Production, 2026)

Enhancement of vitamin B12 in plant-based food through microbial fermentation-a sustainable food system - Gitanjali S. Deokar; Vaishnavi A. Pathak; Sanjay J. Kshirsagar; Fahad Al-Asmari; Nilesh Nirmal (Food Chemistry, 2025)

Synergistic Effects of Pollarding and Chlormequat Chloride on Growth, Yield, Quality, and Pest-Disease Incidence in Papaya cv. F1-Red Lady Under Controlled Cultivation - Suvrajit Patra; Sonu Nagar; K. M. Renuka Swamy; Anshuman Pathak; Neeharika Kanth; Sanjay Kumar Singh; Gangadhar Nanda; Asish Kumar Panda (Journal of Plant Growth Regulation, 2025)

Effect of metakaolin and lime addition on geopolymerization of construction and demolition waste - Arvind Pathak; Sanjay Kumar; Vinay Kumar Jha (Environmental Science and Pollution Research, 2024)

Fabrication of magnetite/GO/potassium copper hexacyanoferrate nanocomposite for removal of radioactive cesium ions - Isha Riyal; Krishan Kant Singh; Archana Ramola; Jyoti Rawat; Sanjay Kumar Pathak; Surajit Panja; Himani Sharma; Charu Dwivedi (Journal of Environmental Radioactivity, 2024)

Source separation of urine and treatment: Impact on energy consumption, greenhouse gas emissions, and decentralised wastewater treatment process - Umakant Badeti; Jiaxi Jiang; Sanjay Kumarasingham; Abdulaziz Almuntashiri; Niren Kumar Pathak; Amit Chanan; Stefano Freguia; Wei Lun Ang; Noreddine Ghaffour; Ho Kyong Shon; Sherub Phuntsho (Desalination, 2024)

Fatty Acids and their Proteins in Adipose Tissue Inflammation - Rahul Mallick; Sanjay Basak; Ranjit K. Das; Antara Banerjee; Sujay Paul; Surajit Pathak; Asim K. Duttaroy (Cell Biochemistry and Biophysics, 2024)
Chronic low-grade adipose tissue inflammation is associated with metabolic disorders. Inflammation results from the intertwined cross-talks of pro-inflammatory and anti-inflammatory pathways in the immune response of adipose tissue. In addition, adipose FABP4 levels and lipid droplet proteins are involved in systemic and tissue inflammation. Dysregulated adipocytes help infiltrate immune cells derived from bone marrow responsible for producing cytokines and chemokines. When adipose tissue expands in excess, adipocyte exhibits increased secretion of adipokines and is implicated in metabolic disturbances due to the release of free fatty acids. This review presents an emerging concept in adipose tissue fat metabolism, fatty acid handling and binding proteins, and lipid droplet proteins and their involvement in inflammatory disorders.

SPAD Chlorophyll Meter-Based Real-Time Nitrogen Management in Manure-Amended Lowland Rice - Mainak Ghosh; Arnab Roychowdhury; Swaraj Kumar Dutta; Kali Krishna Hazra; Garima Singh; Anshuman Kohli; Sanjay Kumar; Shivashankar Acharya; Jajati Mandal; Yanendra Kumar Singh; Sushil Kumar Pathak; Sanjeev Kumar Gupta (Journal of Soil Science and Plant Nutrition, 2023)

India's renewable energy research and policies to phase down coal: Success after Paris agreement and possibilities post-Glasgow Climate Pact - Kripal Singh; Ram Swaroop Meena; Sandeep Kumar; Shalini Dhyani; Seema Sheoran; Har Mohan Singh; Vinayak V. Pathak; Zaira Khalid; Anita Singh; Kapil Chopra; Somvir Bajar; Faiz Ahmad Ansari; et al. (Biomass and Bioenergy, 2023)

Functionality of fructosphere bacteria Kocuria sediminis strain AC3 in plant growth promotion and biodegradation of the acephate in grape berries - Yogita H. Ranade; Sujoy Saha; Madhura Chandrashekar; Indu Sanjay Sawant; Raviraj C. Shinde; Pranav D. Pathak (Biologia, 2022)

Phytochemical Analysis of Indian Stinging Plants: An Initiative Towards Development of Future Novel Biothreat Agents for Self-defence - Sanjay Mohan Gupta; Kamal Kumar; Rakshit Pathak (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Risk factors and impact of retained fetal membranes on performance of dairy bovines reared under subtropical conditions - Susavi Kumari; Shiv Prasad; Arumugam Kumaresan; Ayyasamy Manimaran; Tapas Kumar Patbandha; Rupal Pathak; Prasanta Boro; Tushar Kumar Mohanty; Sanjay Kumar Ravi (Tropical Animal Health and Production, 2015)

Complete nucleotide sequence of the envelope gene of pseudocowpox virus isolates from Indian dromedaries (Camelus dromedarius) - G. Nagarajan; S. K. Ghorui; Sanjay Kumar; K. M. L. Pathak (Archives of Virology, 2010)